Implementation of Primary Service Integration to Improve Posyandu Performance in Ciwuni Village, Kesugihan - Rahmawati, Lusiana Dwi; Julietta, Cut Sayla Trizki; Yunilasari, Dita; Putri, Fika Meliana; Saputro, Rahmatullah Hasan; Azzara, Suci Nabila; Aji, Sadewa Kamara; Anugraeni, Yuliza Hera Tri; Pradianita, Aurelia Anaya Dwi; Yudha, Gading Prawira; Susanti, Rini Puji; Saputra, Wildan Aji (Proceedings Series on Social Sciences & Humanities, 2025)
Primary Health Care Integration (ILP) is a strategy to strengthen basic health services by integrating various health programs into a unified, integrated system at the village level. Ciwuni Village, Kesugihan Subdistrict, Cilacap Regency has the potential to develop ILP through the optimal utilization of Posyandu (community health posts), but still faces challenges such as limited capacity of health workers, inadequate facilities, and insufficient community participation. This initiative aims to improve the implementation of ILP by empowering health workers, conducting comprehensive health examinations, providing education to the community, and strengthening the referral system. The methods applied include training for health workers, on-site mentoring, and evaluations of their knowledge and skills before and after the implementation of the activities.